Intestinal Development and Histomorphometry of Broiler Chickens Fed Trichoderma reesei Degraded Date Seed Diets - Alyileili, Salem R.; El-Tarabily, Khaled A.; Belal, Ibrahim E. H.; Ibrahim, Wissam H.; Sulaiman, Mohsin; Hussein, Ahmed S. (Frontiers in Veterinary Science, 2020)
A study was conducted to investigate the impact of degraded date pits (DDP)on the development and morphology of the intestine in broilers. Trichoderma reesei was used to produce the DDP using a solid-state degradation method. One hundred and eighty broilers were divided into six treatments in triplicate groups of 10 chicks each. The dietary treatments were: positive control with corn-soy diet, negative control with corn-soy diet + 20% oxytetracycline at 0.05%, corn-soy + 10% DDP, corn-soy diet + 0.2% mannan oligosaccharides, corn-soy diet + 0.2% mannose and corn-soy diet + 0.1% mannose for six weeks. The results indicate that a 10% DDPdiet increased the activities of the pancreatic enzymes, the villus length, and the villus/crypt ratio and decreased the crypt depth of the intestine. In conclusion,When compared to oxytetracycline and MOS, DDP can be used as a replacement for antibiotic growth promoters for broilers while improving gut development and intestinal health.